The effect of treatment with montelukast on levels of serum interleukin-10, eosinophil cationic protein, blood eosinophil counts, and clinical parameters in children with asthma - Yüksel, Birol; Aydemir, Cumhur; Ustündag, Gonca; Eldeş, Nilüfer; Kutsal, Ebru; Can, Murat; Demirtaş, Selda; Tomaç, Nazan (The Turkish Journal of Pediatrics, 2009)
Interleukin (IL)-10 is an important immunoregulatory and anti-inflammatory cytokine. IL-10 levels are reduced in asthmatic airways. A regulatory mechanism involving IL-4 induced allergen-specific IL-10 production may be defective in allergic subjects, and this defect potentially contributes to more intense inflammation. The aim of this study was to define the effect of treatment with montelukast on serum levels of IL-10, eosinophil cationic protein (ECP), blood eosinophil counts, and clinical parameters (symptom score and lung function tests) in children with mild and moderate persistent asthma. Twenty-five children with mild-to-moderate persistent asthma and 25 nonatopic healthy children as controls were enrolled in the study. Patients were treated with montelukast for four weeks. Lung function tests for forced expiratory volume in 1 second (FEV1), peak expiratory flow (PEF), and forced expiratory flow between 25% and 75% (FEF25-75) were performed before and after treatment. Serum IL-10, ECP levels, and blood eosinophil counts were determined in both the control group and asthmatic children before and after treatment. The mean serum IL-10 levels were significantly lower before treatment than after treatment (1.75 +/- 0.9 pg/ml and 5.49 +/- 3.6 pg/ml; p < 0.001) and in control subjects (5.6 +/- 2.8 pg/ml). After four weeks of treatment with montelukast, the mean blood eosinophil count value (608 +/- 73/mm3 and 469 +/- 57/mm3; p < 0.05) but not the ECP value (33.98 +/- 24.3 microg/L and 29.03 +/- 19.2 microg/L; p > 0.05) was significantly decreased. After treatment with montelukast, all clinical parameters and lung function tests improved. We found no statistical correlations between the serum level of IL-10 and the serum level of ECP, eosinophil count, lung function tests, or clinical scores after treatment with montelukast. Montelukast caused a statistically significant increase in serum IL-10 levels and decrease in peripheral blood eosinophil counts over the four-week treatment period. Our study indicates that montelukast provides clinical benefits for children with chronic asthma and produces an anti-inflammatory response by increasing serum IL-10 levels,